Method for obtaining surface hydrogen concentration of hydrogen permeation sample by considering hydrogen trap effect

By conducting multiple sets of hydrogen permeation experiments and thermal desorption spectroscopy experiments under different conditions, combining the hydrogen diffusion kinetic equation, the hydrogen trap density and binding energy were calculated, and the hydrogen concentration equilibrium relationship was established, and the hydrogen trap function was solved in the existing technology. The problem of achieving more accurate hydrogen concentration measurement and material performance evaluation.

CN119438027AInactive Publication Date: 2025-02-14ZHEJIANG UNIV

Patent Information

Application Number
CN202411490883.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing electrochemical hydrogen permeation experiments fail to consider the effect of hydrogen trap on the hydrogen diffusion process and surface hydrogen concentration distribution, resulting in a deviation in the hydrogen concentration distribution and affecting the evaluation of the mechanical properties of the materials.

Method used

By conducting multiple sets of hydrogen permeation experiments under different temperatures and hydrogen charging current/pressure, combining the gradual analysis curve and thermal desorption spectral experiments of hydrogen diffusion kinetic equations, the hydrogen trap density and binding energy are calculated, and the lattice hydrogen concentration is established. The equilibrium relationship with trap hydrogen concentration is to accurately calculate the hydrogen concentration on the surface of the hydrogen permeation sample.

Benefits of technology

This method can more accurately obtain the hydrogen concentration on the surface of the hydrogen permeation experimental material, providing a more accurate basis for predicting the internal hydrogen concentration distribution rules of the material and the performance deterioration of the material in a hydrogen-permeable environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119438027A_ABST
    Figure CN119438027A_ABST
Patent Text Reader

Abstract

The invention relates to a material performance testing technology in a hydrogen environment, and aims to provide a method for acquiring the surface hydrogen concentration of a hydrogen permeation sample by considering a hydrogen trap effect. Comprising the following steps: performing multiple groups of hydrogen permeation experiments on a to-be-tested material; fitting a hydrogen permeation curve by using test data to obtain steady-state hydrogen permeation current density and hysteresis diffusion time under different conditions, and calculating the lattice hydrogen concentration of the hydrogen-filled surface; calculating the hydrogen trap density based on the progressive analysis curve of the hydrogen diffusion kinetic equation and the lattice hydrogen diffusion coefficient of the to-be-detected material; calculating the hydrogen trap binding energy of the to-be-tested material according to a thermal desorption spectrum experiment result; and establishing a balance relationship between lattice hydrogen concentration and trap hydrogen concentration, and obtaining a concentration distribution rule in the hydrogen diffusion direction and the hydrogen concentration on the hydrogen charging surface during steady-state diffusion. According to the method, the nonlinear effect, caused by the hydrogen trap effect in the hydrogen permeation process, of hydrogen distribution in the material during steady-state hydrogen diffusion is considered, and the hydrogen concentration on the surface of the hydrogen permeation experiment material can be obtained more accurately.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a material performance testing technology in a hydrogen environment, and in particular to a method for obtaining the hydrogen concentration on the surface of a hydrogen permeation sample taking into account the effect of hydrogen traps. Background Art

[0002] Hydrogen energy is an important part of the future green and low-carbon energy system, and its industrial chain covers preparation, storage, transportation and use. In the storage and transportation of hydrogen energy, high-pressure gaseous hydrogen has been widely used due to its simple structure and mature technology. However, in a high-pressure hydrogen environment, metal materials are prone to hydrogen embrittlement, resulting in a serious decline in mechanical properties, which in turn endangers the safe operation of hydrogen storage and transportation equipment. Existing studies have shown that the degree of hydrogen embrittlement of the material is directly related to the hydrogen concentration. Therefore, it is crucial to obtain and study the hydrogen concentration distribution and evolution of metal materials under simulated service conditions through hydrogen permeation tests in order to evaluate the changes in their mechanical properties in a hydrogen environment during actual service.

[0003] The Devanathan-Stachurski dual electrolytic cell device is widely used in electrochemical hydrogen permeation experiments of metals. If the cathode electrolytic cell in the device is replaced with a high-pressure hydrogen container, gas-phase hydrogen permeation experiments can be carried out. By analyzing the time-hydrogen permeation current curve obtained by the experiment using Fick's diffusion law, parameters such as the apparent hydrogen diffusion coefficient and surface hydrogen concentration of the material can be obtained. However, existing electrochemical hydrogen permeation experiments generally fail to consider the impact of hydrogen trapping on the hydrogen diffusion process and surface hydrogen concentration distribution.

[0004] Hydrogen traps refer to the parts of metal that are easy to adsorb and capture hydrogen atoms. There is an internal stress field around the crystal defects and the second phase inside the steel, which can interact with hydrogen atoms and adsorb hydrogen around them, forming a trap for capturing hydrogen. Due to the existence of hydrogen traps, the actual hydrogen diffusion process of metal materials in a hydrogen environment does not strictly follow Fick's diffusion law, and Fick's second law cannot accurately fit the hydrogen permeation curve.

[0005] The hydrogen concentration in metal materials is divided into lattice hydrogen concentration and trapped hydrogen concentration. The surface hydrogen concentration obtained by the electrochemical hydrogen permeation experiment is the sum of the lattice hydrogen concentration and the trapped hydrogen concentration. Although the lattice diffusion inside the metal material follows Fick's law and presents a linear distribution, the hydrogen trapped does not follow this law, so the actual total hydrogen concentration will also show a nonlinear distribution. At the same time, even when the hydrogen diffusion reaches a steady state, the hydrogen concentration distribution inside the metal material does not necessarily follow Fick's first law, but presents a nonlinear hydrogen distribution, resulting in deviations in the calculated surface hydrogen concentration.

[0006] Therefore, if the nonlinear effect of hydrogen traps on the hydrogen concentration distribution is ignored, it will inevitably affect the accuracy of the hydrogen concentration data on the surface of metal materials in the hydrogen permeation experiment, and thus have a negative impact on the accurate evaluation of the service performance of metal materials. Summary of the invention

[0007] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a method for obtaining the hydrogen concentration on the surface of a hydrogen permeation sample taking into account the effect of hydrogen traps.

[0008] To solve the technical problem, the solution of the present invention is:

[0009] A method for obtaining the surface hydrogen concentration of a hydrogen permeation sample taking into account the effect of hydrogen traps is provided, comprising the following steps:

[0010] (1) Based on the operating conditions of the metal material to be tested, multiple groups of hydrogen permeation experiments are carried out on the material to be tested under different temperatures and hydrogen charging currents / hydrogen charging pressures;

[0011] (2) A series of hydrogen permeation curves reflecting the current-time relationship are obtained by fitting the test data of the hydrogen permeation experiment. The steady-state hydrogen permeation current density and hysteresis diffusion time under different conditions are obtained based on the curves, and the lattice hydrogen concentration on the hydrogen-filled surface of the material to be tested is further calculated.

[0012] (3) Based on the asymptotic analysis curve of the hydrogen diffusion kinetics equation and the lattice hydrogen diffusion coefficient of the material to be tested, the hydrogen trap density N of the material to be tested is calculated. x ;

[0013] (4) Conduct a thermal desorption spectrum experiment on the material to be tested, and calculate the hydrogen trap binding energy E of the material to be tested based on the experimental results b ;

[0014] (5) Based on the lattice hydrogen concentration of the hydrogen-filled surface of the material to be tested Hydrogen trap density N x and hydrogen trap binding energy E b , establish the equilibrium relationship between the lattice hydrogen concentration and the trapped hydrogen concentration in the material to be tested, obtain the concentration distribution law of the hydrogen diffusion direction in the sample during steady-state diffusion, and obtain the hydrogen concentration on the hydrogen-filled surface of the sample to be tested by calculation.

[0015] As a preferred solution of the present invention, the hydrogen permeation experiment in step (1) refers to a liquid phase hydrogen permeation experiment or a high pressure gas phase hydrogen permeation experiment; the hydrogen permeation current curve is a curve of the relationship between the hydrogen permeation current and time obtained in the anode electrolytic cell test during the permeation experiment, and the hysteresis diffusion time refers to the time when the hydrogen diffusion current i p The time corresponding to reaching 0.63 times the steady-state diffusion current.

[0016] As a preferred solution of the present invention, in step (2), the lattice hydrogen concentration of the hydrogen-filled surface of the material to be tested is calculated according to the following formula:

[0017]

[0018] in, is the steady-state hydrogen permeation current density; L is the thickness of the sample; D L is the lattice hydrogen diffusion coefficient of the material to be tested, obtained based on theoretical calculations or hydrogen permeation experiments; F is the Faraday constant.

[0019] As a preferred solution of the present invention, for the material to be tested with a bcc crystal structure, the lattice hydrogen diffusion coefficient D is calculated using the following formula: L :

[0020]

[0021] Wherein, the gas constant R = 8.314 J / (mol·K), and T is the material temperature.

[0022] As a preferred solution of the present invention, in step (3), the hydrogen trap is a reversible hydrogen trap, which corresponds to hydrogen released below 300° C. in a thermal desorption spectrum experiment.

[0023] As a preferred solution of the present invention, in step (3), the hydrogen trap density N of the material to be tested is determined according to the following steps: x :

[0024] (3.1) Calculate the lattice hydrogen occupancy θ of the material to be tested according to the following formula L :

[0025]

[0026] Where: N L is the lattice hydrogen trap site density of the material to be tested, Na is the Avogadro constant, and β is the number of hydrogen atoms that can be accommodated at each lattice site;

[0027] (3.2) Based on the asymptotic analysis curve of the hydrogen diffusion kinetics equation and a series of hydrogen permeation curves, the relationship between the hysteresis diffusion time and the lattice hydrogen occupancy is fitted, and the hydrogen trap density N of the material to be tested is calculated. x .

[0028] As a preferred solution of the present invention, the asymptotic analysis curve of the hydrogen diffusion kinetic equation is divided into 4 intervals, as follows:

[0029]

[0030] Among them, t lagis the hysteresis diffusion time; K is the equilibrium constant between the trap hydrogen concentration and the lattice hydrogen concentration, K = exp(E b / RT); E b is the hydrogen trap binding energy.

[0031] The lattice hydrogen occupancy θ calculated from the hydrogen permeation experiment L and the hysteresis diffusion time t lag Based on the distribution in each interval, the calculation formula for the corresponding interval is selected, and the normalized hydrogen trap density is fitted based on the above formula

[0032] The hydrogen trap density N is calculated according to the following formula: x :

[0033]

[0034] Among them, α is the number of hydrogen atoms accommodated by each hydrogen trap site; β is the number of hydrogen atoms that can be accommodated by each lattice site.

[0035] As a preferred solution of the present invention, the step (4) comprises:

[0036] (4.1) Conduct a series of thermal desorption spectroscopy experiments on the material to be tested to obtain the hydrogen desorption rate curves at different heating rates;

[0037] (4.2) Determine the peak temperature T of the hydrogen desorption rate based on the hydrogen desorption rate curve p ; For the same material, the peak temperature of the heating rate and hydrogen release rate has the following relationship:

[0038]

[0039] Where φ is the heating rate in the thermal desorption spectrum experiment, °C / min; E a is the activation energy of the hydrogen trap; R is the gas constant, 8.314 J / mol / K.

[0040] (4.3) The activation energy E of the hydrogen trap is obtained by linear regression. a The hydrogen trap binding energy E is further calculated according to the following formula b :

[0041] E b =E a -Q

[0042] Among them, Q is the diffusion activation energy of H in α-Fe, 5.69 kJ / mol (a constant).

[0043] As a preferred solution of the present invention, in step (5), the hydrogen concentration of the hydrogen-charged surface of the material to be tested is calculated according to the following steps:

[0044] (5.1) Based on the lattice hydrogen concentration of the hydrogen-filled surface of the material to be tested Hydrogen trap density N x , hydrogen trap binding energy E b , the trapped hydrogen concentration on the hydrogen-charged surface is calculated according to the following formula:

[0045]

[0046] (5.2) Based on the trapped hydrogen concentration on the hydrogen-charged surface and the lattice hydrogen concentration on the hydrogen-charged surface, the hydrogen concentration on the hydrogen-charged surface of the material to be tested is calculated according to the following formula:

[0047]

[0048] Wherein, c0 is the hydrogen concentration of the hydrogen-filled surface of the sample to be tested; is the trapped hydrogen concentration; is the lattice hydrogen concentration.

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] 1. Compared with the existing hydrogen permeation test method, the present invention takes into account the nonlinear effect of hydrogen distribution inside the material during steady-state hydrogen diffusion caused by the hydrogen trap effect during hydrogen permeation. Therefore, the method of the present invention can more accurately obtain the hydrogen concentration on the surface of the hydrogen permeation test material.

[0051] 2. The method based on the present invention can provide a more accurate basis for further predicting the distribution law of hydrogen concentration inside the material and the performance degradation of the material in a hydrogen environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 Flow chart of the experimental process for obtaining the surface hydrogen concentration of the hydrogen permeation sample in the present invention.

[0053] Figure 2 This is the gas phase hydrogen permeation curve of X80 pipeline steel under 1MPa conditions.

[0054] Figure 3 This is the gas phase hydrogen permeation curve of X80 pipeline steel under 4MPa conditions.

[0055] Figure 4 This is the gas phase hydrogen permeation curve of X80 pipeline steel under 8MPa conditions.

[0056] Figure 5 This is the relationship curve between the normalized hysteresis time and the lattice hydrogen occupancy.

[0057] Figure 6 This is the hydrogen desorption rate curve of X80 pipeline steel at different heating rates.

[0058] Figure 7 Linear regression curve of hydrogen trap activation energy of X80 pipeline steel at different heating rates. DETAILED DESCRIPTION

[0059] The method for obtaining the surface hydrogen concentration of a hydrogen permeation sample taking into account the effect of hydrogen traps provided by the present invention can accurately calculate the hydrogen concentration of the hydrogen-filled surface of the sample during the hydrogen permeation experiment, thereby providing support for predicting the mechanical properties of the material in the presence of hydrogen.

[0060] Part I Implementation of the Invention

[0061] The method for obtaining the surface hydrogen concentration of a hydrogen permeation sample taking into account the effect of hydrogen traps provided by the present invention comprises the following steps:

[0062] 1. Based on the working conditions of the metal materials to be tested, multiple groups of hydrogen permeation experiments are carried out on the materials to be tested under different temperatures and hydrogen charging currents / hydrogen charging pressures;

[0063] Hydrogen permeation experiment refers to liquid phase hydrogen permeation experiment or high pressure gas phase hydrogen permeation experiment; hydrogen permeation current curve is the relationship curve between hydrogen permeation current and time obtained in the anode electrolytic cell test during the permeation experiment; hysteresis diffusion time refers to when the hydrogen diffusion current i p The time corresponding to reaching 0.63 times the steady-state diffusion current.

[0064] 2. A series of hydrogen permeation curves reflecting the current-time relationship are obtained by fitting the test data of the hydrogen permeation experiment. The steady-state hydrogen permeation current density and hysteresis diffusion time under different conditions are obtained according to the curves, and the lattice hydrogen concentration on the hydrogen-filled surface of the material to be tested is further calculated according to the following formula:

[0065]

[0066] in, is the steady-state hydrogen permeation current density; L is the thickness of the sample; D L is the lattice hydrogen diffusion coefficient of the material to be tested, obtained based on theoretical calculations or hydrogen permeation experiments; F is the Faraday constant.

[0067] 3. Based on the asymptotic analysis curve of the hydrogen diffusion kinetics equation and the lattice hydrogen diffusion coefficient of the material to be tested, the hydrogen trap density N of the material to be tested is calculated. x ;

[0068] For the material to be tested with a bcc crystal structure, the lattice hydrogen diffusion coefficient D can be calculated using the following formula: L :

[0069]

[0070] Wherein, the gas constant R = 8.314 J / (mol·K), and T is the material temperature.

[0071] The hydrogen trap is a reversible hydrogen trap, which corresponds to hydrogen released below 300° C. in a thermal desorption spectrum experiment.

[0072] Determine the hydrogen trap density N of the material to be tested according to the following steps x :

[0073] (3.1) Calculate the lattice hydrogen occupancy θ of the material to be tested according to the following formula L :

[0074]

[0075] Where: N L is the lattice hydrogen trap site density of the material to be tested, Na is the Avogadro constant, and β is the number of hydrogen atoms that can be accommodated at each lattice site;

[0076] (3.2) Based on the asymptotic analysis curve of the hydrogen diffusion kinetics equation and a series of hydrogen permeation curves, the relationship between the hysteresis diffusion time and the lattice hydrogen occupancy is fitted, and the hydrogen trap density N of the material to be tested is calculated. x .

[0077] The asymptotic analysis curve of the hydrogen diffusion kinetic equation is divided into 4 intervals, as follows:

[0078]

[0079] Among them, t lag is the hysteresis diffusion time; K is the equilibrium constant between the trap hydrogen concentration and the lattice hydrogen concentration, K = exp(E b / RT); E b is the hydrogen trap binding energy.

[0080] The lattice hydrogen occupancy θ calculated from the hydrogen permeation experiment L and the hysteresis diffusion time t lag Based on the distribution in each interval, the calculation formula for the corresponding interval is selected, and the normalized hydrogen trap density is fitted based on the above formula The hydrogen trap density N is further calculated according to the following formula: x :

[0081]

[0082] Here, α is the number of hydrogen atoms accommodated in each hydrogen trap site.

[0083] The idea of ​​this step is to use the lattice hydrogen occupancy θ L As the x-axis, the hysteresis diffusion time tlag As the y-axis, all experimental results are plotted on the same graph; in the above four partitions, a suitable formula is selected to fit the experimental results to obtain the normalized hydrogen trap density.

[0084] 4. Perform thermal desorption spectrum experiment on the material to be tested, and calculate the hydrogen trap binding energy E of the material to be tested based on the experimental results. b ;

[0085] (4.1) Conduct a series of thermal desorption spectroscopy experiments on the material to be tested to obtain the hydrogen desorption rate curves at different heating rates;

[0086] (4.2) Determine the peak temperature T of the hydrogen desorption rate based on the hydrogen desorption rate curve p ; For the same material, the peak temperature of the heating rate and hydrogen release rate has the following relationship:

[0087]

[0088] Where φ is the heating rate in the thermal desorption spectrum experiment, °C / min; E a is the activation energy of the hydrogen trap; R is the gas constant, 8.314 J / mol / K.

[0089] (4.3) The activation energy E of the hydrogen trap is obtained by linear regression. a The hydrogen trap binding energy E is further calculated according to the following formula b :

[0090] E b =E a -Q

[0091] Where Q is the activation energy of H diffusion in α-Fe, 5.69 kJ / mol.

[0092] 5. Based on the lattice hydrogen concentration of the hydrogen-filled surface of the material to be tested Hydrogen trap density N x and hydrogen trap binding energy E b , establish the equilibrium relationship between the lattice hydrogen concentration and the trapped hydrogen concentration in the material to be tested, obtain the concentration distribution law of the hydrogen diffusion direction in the sample during steady-state diffusion, and obtain the hydrogen concentration on the hydrogen-filled surface of the sample to be tested by calculation.

[0093] Calculate the hydrogen concentration of the hydrogen-charged surface of the material to be tested according to the following steps:

[0094] (5.1) Based on the lattice hydrogen concentration of the hydrogen-filled surface of the material to be tested Hydrogen trap density N x , hydrogen trap binding energy E b , the trapped hydrogen concentration on the hydrogen-charged surface is calculated according to the following formula:

[0095]

[0096] (5.2) Based on the trapped hydrogen concentration on the hydrogen-charged surface and the lattice hydrogen concentration on the hydrogen-charged surface, the hydrogen concentration on the hydrogen-charged surface of the material to be tested is calculated according to the following formula:

[0097]

[0098] Wherein, c0 is the hydrogen concentration of the hydrogen-filled surface of the sample to be tested; is the trapped hydrogen concentration; is the lattice hydrogen concentration.

[0099] Part II: A Specific Example

[0100] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in combination with specific examples and drawings. Obviously, the described examples are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0101] Example 1

[0102] like Figure 3 The following is an example of a gas phase hydrogen permeation test of X80 pipeline steel at different temperatures to specifically describe the method for obtaining the surface hydrogen concentration of the hydrogen permeation test sample in this embodiment. The experimental steps include:

[0103] 1. High-pressure gas-phase hydrogen permeation experiments were conducted to carry out hydrogen permeation experiments on X80 pipeline steel at different hydrogen pressures.

[0104] The experimental pressures were 1, 4, and 8 MPa, and the experimental temperatures were -15, -5, 5, 10, 20, 30, 40, 50, and 60 °C. The hydrogen permeation curves obtained were as follows: Figure 2-4 shown.

[0105] 2. According to Figure 2-4 The hydrogen permeation curve in the figure is used to extract the steady-state hydrogen permeation current density i at each temperature. p ∞ , and the hysteresis diffusion time t lag (As shown in Table 1).

[0106] The hysteresis diffusion time refers to the time when the hydrogen diffusion current i p The time corresponding to reaching 0.63 times the steady-state diffusion current (conventional practice).

[0107] Table 1 Steady-state hydrogen permeation current density and hysteresis diffusion time of X80 pipeline steel at different temperatures and pressures

[0108]

[0109] 3. Calculate the lattice hydrogen concentration on the hydrogen-charged surface of the material.

[0110] Since the lattice hydrogen diffusion inside the material follows Fick's law, when the hydrogen diffusion reaches a steady state, the lattice hydrogen concentration inside the material is linearly distributed, and the anode electrolytic cell on the outlet side can promptly oxidize the infiltrated hydrogen atoms into hydrogen ions, so the lattice hydrogen concentration on the outlet surface is 0.

[0111] At this time, the lattice hydrogen concentration on the hydrogen-filled surface of the sample is for:

[0112]

[0113] Wherein, L is the thickness of the hydrogen permeated sample; in this example, the thickness L of the hydrogen permeated sample is 0.2 cm, and the Faraday constant F=96485 C / mol.

[0114] For bcc structure materials such as X80, the lattice hydrogen diffusion coefficient D L The following formula can be used for calculation:

[0115]

[0116] Wherein, the gas constant R = 8.314 J / (mol·K), and T is the material temperature.

[0117] The calculation results of the lattice hydrogen concentration of this example are shown in Table 2.

[0118] Table 2 Lattice hydrogen concentration of X80 pipeline steel at different temperatures and pressures

[0119]

[0120] By fitting the above test results, the general expression relationship of the surface lattice hydrogen concentration of X80 pipeline steel at different temperatures and pressures can be obtained as follows:

[0121]

[0122] 4. Lattice hydrogen occupancy of the material to be tested The number of hydrogen atoms that can be accommodated at each lattice site is β = 1, and the Avogadro constant Na = 6.02×10 23 , the lattice hydrogen trap site density N in bcc materials L =5.2×10 23 sites / cm 3The calculation results of this example are shown in Table 3.

[0123] Table 3 Lattice hydrogen occupancy of X80 pipeline steel at different temperatures and pressures

[0124]

[0125]

[0126] 5. Based on the hysteresis diffusion time t lag , calculate the normalized hysteresis time D L t lag / L 2 .

[0127] 6. Use the asymptotic analysis curve based on the hydrogen diffusion kinetic equation to fit the lattice hydrogen occupancy θ L The relationship between the normalized hysteresis time and Figure 5 As shown:

[0128] Among them, the asymptotic analysis curve based on the hydrogen diffusion kinetic equation is as follows, which is divided into 4 intervals

[0129]

[0130] in is the normalized hydrogen trap density.

[0131] In this example, the lattice hydrogen occupancy θ L and the hysteresis diffusion time t lag All data points fall in interval II.

[0132] Therefore, the normalized hydrogen trap density is obtained by fitting the equation, and the hydrogen trap density is further calculated:

[0133]

[0134] The number of hydrogen atoms accommodated in each hydrogen trap site is α=1.

[0135] The calculated hydrogen trap density of X80 pipeline steel is 5.08×10 16 sites / cm 3 .

[0136] 7. Thermal desorption spectrum experiments of X80 pipeline steel were carried out at different heating rates to obtain the hydrogen desorption rate curves of X80 pipeline steel at different heating rates, such as Figure 6 shown.

[0137] 8. According to the hydrogen desorption rate curve, find the peak temperature T of the hydrogen desorption rate p .

[0138] For the same material, the peak temperature of the heating rate and hydrogen release rate has the following relationship:

[0139]

[0140] Where φ is the heating rate in the thermal desorption spectroscopy experiment (℃ / min).

[0141] like Figure 7 As shown in Figure 2, the activation energy E of hydrogen traps in X80 pipeline steel can be determined by linear regression. a =51.77 kJ / mol. Further calculation of hydrogen trap binding energy E b =E a -5.69 = 46.08 kJ / mol. (5.69 is a constant value, which is the activation energy of H diffusion in α-Fe)

[0142] 9. Based on the hydrogen trap binding energy, hydrogen trap site density and lattice hydrogen concentration on the hydrogen-charged surface, the trapped hydrogen concentration on the hydrogen-charged surface of X80 pipeline steel is calculated as follows:

[0143]

[0144] The settlement results are shown in Table 4.

[0145] 10. Calculate the total hydrogen concentration on the hydrogen-filled surface of X80 pipeline steel:

[0146]

[0147] The settlement results are shown in Table 4.

[0148] Table 4 Steady-state hydrogen permeation current density and hysteresis diffusion time of X80 pipeline steel at different temperatures and pressures

[0149]

[0150] Example 2 (Verification of the method of the present invention and comparison with existing methods)

[0151] In order to verify the accuracy of the method described in the present invention, X80 pipeline steel was charged with hydrogen for 24 hours at temperatures of 20, 40, and 60°C and hydrogen pressures of 1 and 8 MPa, respectively, to ensure that the hydrogen inside the material reached a saturated state. The sample was then taken out of the autoclave and the hydrogen content inside the sample was analyzed by thermal desorption spectroscopy. The experimental results are shown in Table 5.

[0152] Table 5 Saturated hydrogen content of X80 pipeline steel at different temperatures and pressures

[0153]

[0154] In the gas phase hydrogen charging experiment, since all surfaces of the sample are in direct contact with high-pressure hydrogen, when the material is saturated with hydrogen, the hydrogen concentration inside the material should be equal everywhere. At this time, the surface hydrogen concentration of the material is consistent with the hydrogen concentration of the entire material. Therefore, under the same temperature and pressure, the hydrogen concentration tested by the thermal desorption spectrum experiment can be used to verify the surface hydrogen concentration calculated based on the hydrogen permeation experiment.

[0155] In order to demonstrate the advantages of this method over existing methods, the widely used linear calculation method is used to calculate the surface hydrogen concentration of X80 pipeline steel at different temperatures and pressures.

[0156] 1. Based on the obtained hysteresis diffusion time, the apparent hydrogen diffusion coefficient of the material is calculated using the following formula:

[0157]

[0158] 2. Based on the obtained apparent hydrogen diffusion coefficient and steady-state hydrogen permeation current density, the apparent surface hydrogen concentration of the material is calculated using the following formula:

[0159]

[0160] The above calculation results are shown in Table 6.

[0161] Table 6 Surface hydrogen concentration of X80 steel calculated by traditional method

[0162]

[0163] The verification results obtained by the traditional method, the method described in the present invention and the thermal desorption experiment are compared, as shown in Table 7.

[0164] Table 7 Comparison of hydrogen concentration between different methods

[0165]

[0166] From the above data, it can be seen that compared with the thermal desorption experiment, the result obtained by the traditional hydrogen concentration calculation method is significantly larger, and it cannot correctly reflect the effect of temperature on the surface hydrogen concentration. The hydrogen embrittlement analysis based on this result may be too conservative. In contrast, the new method proposed in the present invention is more consistent with the hydrogen concentration obtained by the thermal desorption experiment, and can reflect the trend that the total hydrogen concentration on the material surface increases with increasing temperature.

[0167] It should be noted that the present invention uses specific examples to illustrate the principles and implementation methods of the present invention. The above examples are only used to help understand the method and core ideas of the present invention. At the same time, for those skilled in the art, according to the ideas of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A method for obtaining the surface hydrogen concentration of a hydrogen permeation sample taking into account the effect of hydrogen traps, characterized in that: The following steps are involved: (1) Based on the operating conditions of the metal material to be tested, multiple groups of hydrogen permeation experiments are carried out on the material to be tested under different temperatures and hydrogen charging currents / hydrogen charging pressures; (2) A series of hydrogen permeation curves reflecting the current-time relationship are obtained by fitting the test data of the hydrogen permeation experiment. The steady-state hydrogen permeation current density and hysteresis diffusion time under different conditions are obtained based on the curves, and the lattice hydrogen concentration on the hydrogen-filled surface of the material to be tested is further calculated. (3) Based on the asymptotic analysis curve of the hydrogen diffusion kinetics equation and the lattice hydrogen diffusion coefficient of the material to be tested, the hydrogen trap density N of the material to be tested is calculated. x ; (4) Conduct a thermal desorption spectrum experiment on the material to be tested, and calculate the hydrogen trap binding energy E of the material to be tested based on the experimental results b ; (5) Based on the lattice hydrogen concentration of the hydrogen-filled surface of the material to be tested Hydrogen trap density N x and hydrogen trap binding energy E b , establish the equilibrium relationship between the lattice hydrogen concentration and the trapped hydrogen concentration in the material to be tested, obtain the concentration distribution law of the hydrogen diffusion direction in the sample during steady-state diffusion, and obtain the hydrogen concentration on the hydrogen-filled surface of the sample to be tested by calculation.

2. The method according to claim 1, characterized in that: The hydrogen permeation experiment in step (1) refers to a liquid phase hydrogen permeation experiment or a high pressure gas phase hydrogen permeation experiment; the hydrogen permeation current curve is a curve of the relationship between the hydrogen permeation current and time obtained in the anode electrolytic cell test during the permeation experiment, and the hysteresis diffusion time refers to the time when the hydrogen diffusion current i p The time corresponding to reaching 0.63 times the steady-state diffusion current.

3. The method according to claim 1, characterized in that: In step (2), the lattice hydrogen concentration of the hydrogen-filled surface of the material to be tested is calculated according to the following formula: in, is the steady-state hydrogen permeation current density; L is the thickness of the sample; D L is the lattice hydrogen diffusion coefficient of the material to be tested, obtained based on theoretical calculations or hydrogen permeation experiments; F is the Faraday constant.

4. The method according to claim 3, characterized in that For the material to be tested with a bcc crystal structure, the lattice hydrogen diffusion coefficient D is calculated using the following formula: L : Wherein, the gas constant R = 8.314 J / (mol·K), and T is the material temperature.

5. The method according to claim 1, characterized in that: In the step (3), the hydrogen trap is a reversible hydrogen trap, which corresponds to hydrogen released below 300° C. in a thermal desorption spectrum experiment.

6. The method according to claim 1, characterized in that: In step (3), the hydrogen trap density N of the material to be tested is determined according to the following steps: x : (3.1) Calculate the lattice hydrogen occupancy θ of the material to be tested according to the following formula L : Where: N L is the lattice hydrogen trap site density of the material to be tested, Na is the Avogadro constant, and β is the number of hydrogen atoms that can be accommodated at each lattice site; (3.2) Based on the asymptotic analysis curve of the hydrogen diffusion kinetics equation and a series of hydrogen permeation curves, the relationship between the hysteresis diffusion time and the lattice hydrogen occupancy is fitted, and the hydrogen trap density N of the material to be tested is calculated. x .

7. The method according to claim 6, characterized in that The asymptotic analysis curve of the hydrogen diffusion kinetic equation is divided into 4 intervals, as follows: Among them, t lag is the hysteresis diffusion time; K is the equilibrium constant between the trap hydrogen concentration and the lattice hydrogen concentration, K = exp(E b / RT); E b is the hydrogen trap binding energy; The lattice hydrogen occupancy θ calculated from the hydrogen permeation experiment L and the hysteresis diffusion time t lag Based on the distribution in each interval, the calculation formula for the corresponding interval is selected, and the normalized hydrogen trap density is fitted based on the above formula The hydrogen trap density N is calculated according to the following formula: x : Among them, α is the number of hydrogen atoms accommodated by each hydrogen trap site; β is the number of hydrogen atoms that can be accommodated by each lattice site.

8. The method according to claim 1, characterized in that The step (4) comprises: (4.1) Conduct a series of thermal desorption spectroscopy experiments on the material to be tested to obtain the hydrogen desorption rate curves at different heating rates; (4.2) Determine the peak temperature T of the hydrogen desorption rate based on the hydrogen desorption rate curve p ; For the same material, the peak temperature of the heating rate and hydrogen release rate has the following relationship: Where φ is the heating rate in the thermal desorption spectrum experiment, °C / min; E a is the activation energy of the hydrogen trap; R is the gas constant, 8.314 J / mol / K; (4.3) The activation energy E of the hydrogen trap is obtained by linear regression. a The hydrogen trap binding energy E is further calculated according to the following formula b : AND b =And a -Q Where Q is the activation energy of H diffusion in α-Fe, 5.69 kJ / mol.

9. The method according to claim 1, characterized in that: In step (5), the hydrogen concentration of the hydrogen-charged surface of the material to be tested is calculated according to the following steps: (5.1) Based on the lattice hydrogen concentration of the hydrogen-filled surface of the material to be tested Hydrogen trap density N x , hydrogen trap binding energy E b , the trapped hydrogen concentration on the hydrogen-charged surface is calculated according to the following formula: (5.2) Based on the trapped hydrogen concentration on the hydrogen-charged surface and the lattice hydrogen concentration on the hydrogen-charged surface, the hydrogen concentration on the hydrogen-charged surface of the material to be tested is calculated according to the following formula: Wherein, c0 is the hydrogen concentration of the hydrogen-filled surface of the sample to be tested; is the trapped hydrogen concentration; is the lattice hydrogen concentration.

Citation Information

Patent Citations

  • A method for measuring hydrogen trap activation energy of austenitic stainless steel

    CN109190238A

  • Device and method for dynamically measuring hydrogen trap parameters of metal material

    CN111044584A

  • Hydrogen diffusion prediction method and device for hydrogen service material, medium and product

    CN118549299A

Cited By

  • Hydrogen trap characteristic parameter determination method based on genetic algorithm

    CN120613053A